Dietary intake and dietary diversity of adults and children in the North West region of Cameroon: A comparative study - Faith A. Akob; Kirthee Pillay; Nicky Wiles; Muthulisi Siwela (World Nutrition)
Background Improving dietary intake and dietary diversity (DD) among vulnerable populations is currently a global concern. Data on the dietary intake and DD of people living in the North West Region (NWR) of Cameroon is scarce. Objective The objective of the present study was to assess and compare dietary intake and DD of four selected NWR communities. Methods A cross-sectional study design was used to assess the dietary intake and DD of a total of 156 adults (18-65 years old) and 156 children (1-5 years old) from two rural areas (Mankon and Mendakwe) and two urban areas (Mankon and Nkwen). Data were collected using a food frequency questionnaire and an individual household dietary diversity questionnaire. Results In both the urban and rural areas, diets consisted predominantly of refined carbohydrates, fats and oils with a low intake of dairy and fruit and vegetables. The food items that were seldom consumed in both rural and urban areas were brown bread, brown rice and millet as well as some fruits and vegetables. Adults and children from both rural and urban areas of the NWR achieved DD, as indicated by a cut-off point of 5 out of 9 food groups consumed over a 24-hour period. Nevertheless, intakes of dietary fibre and micronutrients were low. Conclusions Although DD was achieved, there is a need to implement strategies to improve the intake of dietary fibre and micronutrients.